High school [1968] - Wiseman, Frederick (Cambridge, MA : Zipporah Films,., 2007)
A documentary study of Northeast High School in Philadelphia in 1968; deals with the ideology and values of a large urban high school as seen through encounters between students, teachers, and parents in guidance sessions, college counseling, discipline, faculty meetings, corridor patrol, gymnasium, and classroom activities.
film
Keywords: Wiseman, Frederick